A fitting-extrapolation method of B-H curve for magnetic saturation applications - Wang, Lichao; Ding, Fuyan; Yang, Dongbo; Wang, Ke; Jiao, Biaoqiang; Chen, Qian (Compel, 2023)
Purpose This paper aims to provide a new method of generating relatively accurate and smooth saturated B-H curves based on reliable measurement data to improve the accuracy and efficiency of electromagnetic simulation. Design/methodology/approach The characteristics of different B-H curve extrapolation models are summarized, and an improved method is proposed. The fitting procedure in low fields and extrapolation procedure in high fields are presented in detail. The saturated B-H curves generated by various methods are compared and discussed. Finally, a simulation case study proved the advantages of the new method in terms of simulation accuracy and efficiency. Findings The B-H curve created by the new method avoids extrapolation from a single point and simultaneously smoothens the entire B-H curve, thereby improving the simulation accuracy and efficiency. The low magnetic potential requirements for closed measurements and the small deviation with open measurements indicate that this method is well-suited for implementation. Research limitations/implications The results are applicable for materials subject to such excitation levels that saturation has to be taken into account. Originality/value While some extrapolation models of B-H curves have been investigated in reference papers, there is still room for improvement in accuracy and smoothness. The new method processes low fields and high fields magnetization data and then connects them based on third-order boundary equations for the first time. This method can generate saturated B-H curves with good accuracy and smoothness while retaining outstanding operability.